2022
DOI: 10.1002/jso.26932
|View full text |Cite
|
Sign up to set email alerts
|

T‐stage downstaging of locally advanced rectal cancer after neoadjuvant chemoradiotherapy is not associated with reduced recurrence after adjusting for tumour characteristics

Abstract: Background and Objectives: Prior studies examining prognostic outcomes of locally advanced rectal adenocarcinomas achieving a complete pathological response following neoadjuvant chemoradiotherapy (nCRT) did not adjust for adverse prognostic factors in multivariate analyses and account for magnetic resonance imaging tumour staging inaccuracy pre-nCRT. We aimed to clarify prognostic outcomes in mT3 rectal adenocarcinomas with ypT-downstaging post-nCRT in robust adjusted analyses.Methods: Retrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The study by Hayes et al showed similar results. [ 32 ] Their investigation on 528 rectal cancer patients showed that even in the absence of adverse prognostic factors, ypT downstaging was not associated with reduced tumor recurrence. [ 32 ] This is in accordance with our finding that the LARC patients were more than 2 times more likely to have a tumor relapse with the positive ypN status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Hayes et al showed similar results. [ 32 ] Their investigation on 528 rectal cancer patients showed that even in the absence of adverse prognostic factors, ypT downstaging was not associated with reduced tumor recurrence. [ 32 ] This is in accordance with our finding that the LARC patients were more than 2 times more likely to have a tumor relapse with the positive ypN status.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] Their investigation on 528 rectal cancer patients showed that even in the absence of adverse prognostic factors, ypT downstaging was not associated with reduced tumor recurrence. [ 32 ] This is in accordance with our finding that the LARC patients were more than 2 times more likely to have a tumor relapse with the positive ypN status. American joint comitee on cancer recommends harvesting a minimum of 12 lymph nodes in the surgical specimens to ensure the adequacy of surgery in CRC patients.…”
Section: Discussionmentioning
confidence: 99%